Interpretasi Ayat-ayat Pendidikan Anak dalam Al-Qur’an dan Implementasinya dalam Keluarga: Studi Tafsir Maudhuí - Nurindah Sari; Dadan Rusmana (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to examine and analyze verses relating to the concept of child education in the Qur'an and its implementation in the family. The research method used in this research is qualitative research through literature review using a maudhui interpretation approach. This study concludes that there are six terms for children in the Qur'an, including ghulam, walad, dzurriyah, ibn, tifl, and shabiy, each of which has a correlation with the concept of children's education. The concept of child education states that in educating children, parents are the first milestone in educating children, in this case the family plays an important role in the education process. In addition, in the concept of educating children there are also methods that must be considered. Among these methods are: 1) the exemplary method; 2) Habituation Method; 3) The method of advice; and 4) monitoring methods. This study recommends that more in-depth research and analysis be carried out with more applicable theories.